(untitled) (Journal of the College of Basic Education, 2022)
The research aims to know the effect of using blended learning on student achievement and information retention for fifth grade students in Biology.One of the preparatory schools for Baghdad city center was chosen randomly, and two classes were chosen randomly, one of which represented the experimental group taught according to blended learning, and another class representing the control group taught according to traditional learning. The sample size was (60) students, after excluding the statistically failed students (5), so that the number of members of each group became (30) students.